2000
DOI: 10.1590/s0001-37652000000100014
|View full text |Cite
|
Sign up to set email alerts
|

Cell damage and neurogenesis in the dentate granule cell layer of adult rats after pilocarpine- or kainate-induced status epilepticus

Abstract: Presented by A.C.M. PaivaDentate granule cells are generally considered to be relatively resistant to excitotoxicity and have been associated to robust synaptogenesis after neuronal damage. Synaptic reorganization of dentate granule cell axons, the mossy fibers, has been suggested to be relevant for hyperexcitability in human temporal lobe epilepsy and animal models. A recent hypothesis has suggested that mossy fiber sprouting is dependent on newly formed dentate granule cells. However, we have recently demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 27 publications
5
27
0
1
Order By: Relevance
“…Taken together, these data are also consistent with our observation that the dentate GCL remained relatively intact compared to other cellular subfields in the hippocampus of KA-treated rats (Fig. 3), and in line with previous reports showing that dentate granule cells appear to be more resistant than other hippocampal neurons to KA-induced SE (Covolan et al, 2000; Hattiangady et al, 2004). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, these data are also consistent with our observation that the dentate GCL remained relatively intact compared to other cellular subfields in the hippocampus of KA-treated rats (Fig. 3), and in line with previous reports showing that dentate granule cells appear to be more resistant than other hippocampal neurons to KA-induced SE (Covolan et al, 2000; Hattiangady et al, 2004). …”
Section: Resultssupporting
confidence: 93%
“…KA-induced SE led to moderate to considerable cell loss and disruption of cellular architecture in CA1, CA3, and the hilus of both CON and SUP rats, which can be seen in Figure 3. In contrast, there was mild to no cell loss in the GCL of the dentate gyrus, which is consistent with previous reports using the KA model of SE (Covolan et al, 2000). We used total hippocampal volume estimates to quantify hippocampal cell loss.…”
Section: Resultssupporting
confidence: 92%
“…Similar increases have been demonstrated in other rodent models of seizures, such as those induced by amygdala kindling [16] and by electroconvulsive shock [17]. Status epilepticus elicited in rats by administration of chemoconvulsants such as pilocarpine, kainic acid or pentylenetetrazole also increases neurogenesis [18,19]. A recent study shows that hippocampal neurogenesis is also stimulated after early-life febrile seizures induced by exposing young rat pups to a hyperthermia treatment [20,21].…”
Section: Introductionsupporting
confidence: 63%
“…Of particular interest in the current context are two recent studies using different experimentally induced forms of damage. Covolan et al (2000) reported an increase in the number of BrdU + cells in sections that would contain the NQZ (in sections 2.45 mm posterior to Bregma) after kainate-and pilocarpine-induced seizures. Conversely, Choi et al (2003), using a transient forebrain ischaemia model, found that the number of BrdU + cells increased in all sectors of the dentate gyrus, except the rostral suprapyramidal blade.…”
Section: Regional Variations In Neurogenesis After Injurymentioning
confidence: 99%